2020
DOI: 10.1016/s1473-3099(19)30401-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying risks and interventions that have affected the burden of diarrhoea among children younger than 5 years: an analysis of the Global Burden of Disease Study 2017

Abstract: Summary Background Many countries have shown marked declines in diarrhoeal disease mortality among children younger than 5 years. With this analysis, we provide updated results on diarrhoeal disease mortality among children younger than 5 years from the Global Burden of Diseases, Injuries, and Risk Factors Study 2017 (GBD 2017) and use the study’s comparative risk assessment to quantify trends and effects of risk factors, interventions, and broader sociodemographic development on mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 31 publications
1
93
0
Order By: Relevance
“…Our nding underpin the conclusion made by different studies (38), and also an ecological study conducted for 193 countries indicated that increasing access to improved sanitation was signi cantly associated with decreased infant mortality rate (39). Similarly, those responsible for the largest declines (13.3%) in the diarrhoea mortality rate were reduction in exposure to unsafe sanitation in children (40). As of 2016, access to improved sanitation in Ethiopia remains alarmingly low with an estimated coverage of 6.3% (35), and more effort is needed.…”
Section: Discussionsupporting
confidence: 78%
“…Our nding underpin the conclusion made by different studies (38), and also an ecological study conducted for 193 countries indicated that increasing access to improved sanitation was signi cantly associated with decreased infant mortality rate (39). Similarly, those responsible for the largest declines (13.3%) in the diarrhoea mortality rate were reduction in exposure to unsafe sanitation in children (40). As of 2016, access to improved sanitation in Ethiopia remains alarmingly low with an estimated coverage of 6.3% (35), and more effort is needed.…”
Section: Discussionsupporting
confidence: 78%
“…We even predicted the highest road-injury-related hospitalization cases in the North-East region during the summer peaks. In the case of diarrheal diseases, estimated to be the leading cause of death globally and having a declining incidence [69,70], we only noticed a slight reduction in new cases over the period 2008-2018 and predicted further stable counts. Finally, tuberculosis, with Romania known to have the highest incidence of extensively drug-resistant tuberculosis in the European Union [71], displayed promising declining hospitalization cases over the years.…”
Section: Discussionmentioning
confidence: 73%
“…Diarrhea is a major cause of morbidity and mortality among under five children worldwide, responsible for an estimated death of 533 768 under 5 children in 2017 [ 1 – 3 ] It is also the leading cause of illness and death among children younger than 5 years in low and middle income countries [ 4 , 5 ], accounts for an estimated 17.5–21% of all deaths in children under the age 5 years. Of all child deaths from diarrhea, 78% occur in the African and South-East Asian regions, which are also disproportionately burdened with infant and childhood HIV infections [ 6 ].…”
Section: Introductionmentioning
confidence: 99%